Reliability and validity of the Turkish version of Loneliness at Work Scale [İş yaşaminda yalnizlik ölçeǧi Türkçe formunun geçerlilik ve güvenilirlik çalişmasi] - (:unkn) unknown (My University, 2009)
Objective: Loneliness at Work Scale (LAWS) was developed to measure loneliness at work by Wright, Burt and Strongman. The purpose of the present study was to investigate the psychometric properties of Turkish version of the LAWS. Methods: Four hundred and thirty-six employees (254 females, 182 males) participated in the study. The study was conducted with the sample consisted of employee with an age range between 18 and 52. The psychometric properties of scale were investigated by test re-test, Cronbach's alpha, exploratory and confirmatory factor analysis and criterion related validity methods. Job Satisfaction Scale and Organizational Commitment Scale were used for the criterion related validity. Results: In order to determine the construct validity of LAWS, exploratory and confirmatory factor analysis was conducted. The factor analysis resulted in two factors; emotional deprivation and social companionship, which is same factor structure as the original form. The Cronbach's alpha for the LAWS was 0.91, emotional deprivation was 0.87 and social companionship was 0.83. The computed test re-test reliability coefficient was found to be 0.82 for the LAWS, 0.78 for emotional deprivation and 0.80 for social companionship. As a concurrent validity, the correlation between LAWS and job satisfaction was -0.34, between LAWS and organizational commitment was -0.29. Conclusion: The psychometric properties of the Turkish version of LAWS showed that a satisfactory level of reliability and validity in Turkish employee.
Keywords: Loneliness at Work Scale (LAWS); Reliability; Validity